Modeling and Finite Element Analysis Simulation of MEMS Based Acetone Vapor Sensor for Noninvasive Screening of Diabetes - Dennis, J.O. (Hindawi Limited, 2016)
Diabetes is currently screened invasively by measuring glucose concentration in blood, which is inconvenient. This paper reports a study on modeling and simulation of a CMOS-MEMS sensor for noninvasive screening of diabetes via detection of acetone vapor in exhaled breath (EB). The sensor has two structures: movable (rotor) and fixed (stator) plates. The rotor plate is suspended on top of the stator by support of four flexible beams and maintaining certain selected initial gaps of 5, 6, 7, 8, 9, 10, or 11 Î¼m to form actuation and sensing parallel plate capacitors. A chitosan polymer of varied thicknesses (1-20 Î¼m) is deposited on the rotor plate and modeled as a sensing element for the acetone vapor. The minimum polymer coating thickness required to detect the critical concentration (1.8 ppm) of acetone vapor in the EB of diabetic subjects is found to be 4-7 Î¼m, depending on the initial gap between the rotor and stator plates. However, to achieve sub-ppm detection limit to sense the acetone vapor concentration (0.4-1.1 ppm) in the EB of healthy people, up to 20 Î¼m polymer thickness is coated. The mathematically modeled results were verified using the 2008 CoventorWare simulation software and a good agreement within a 5.3 error was found between the modeled and the simulated frequencies giving more confidence in the predicted results. Â© 2016 John Ojur Dennis et al.